Pengaruh Orientasi Pelanggan, Kepuasan Pelanggan, Kualitas Pelayanan Terhadap Loyalitas Pelanggan Mobile Banking Wilayah Jabodetabek - Ratna Indah Komalasari; Unik Dwi Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid growth of the banking sector in Indonesia encourages intense competition between financial institutions. In this effort, banks must provide the best service (service excellent) to win the increasingly fierce competition. Therefore, improving service quality is crucial for banks to continue to compete and survive in this competitive banking industry. Providing superior banking services is the main key to ensuring the success of the mobile banking platform and meeting customer needs properly. This study aims to explore the effect of customer orientation, service quality, and customer satisfaction, on customer loyalty for mobile banking customers in JABODETABEK. This research is a quantitative study that uses a purposive sampling method and involves 188 female mobile banking users in JABODETABEK Indonesia. The results showed that the biggest influence, namely customer orientation, had a significant effect on customer satisfaction. Customer orientation affects service quality. Service quality has a positive effect on customer loyalty. Customer satisfaction has a positive effect on customer loyalty. Service quality does not affect customer satisfaction. The next result is that service quality does not mediate customer orientation and customer satisfaction. Customer satisfaction does not mediate service quality and customer loyalty. Future research is expected to use more specific respondents with different measurement techniques. Banks need to ensure that the mobile banking services provided achieve high-quality standards, including speed, reliability, security, and ease of use.